Description of new fossil Squamata from Lajedo de Soledade, Rio Grande do Norte Quaternary: integrating comparative analyses of extant and fossils using geometric morphometrics - Lomba, Sílvia Oliveira (2023)
Squamata is a diverse clade consisting of snakes, lizards, and amphisbaenians. The fossil record of this group is extensive and, in Brazil, extends from the Cretaceous to the Quaternary. These records are mainly composed of fragmented materials, which makes identification a challenging task and dependent on access to extensive scientific collections for them to be appropriately identified. The present work involves identifying Squamata fossils collected in Lajedo de Soledade, Rio Grande do Norte. The analyses were carried out through detailed morphological comparisons and the application of twodimensional geometric morphometry. Geometric morphometry analyses are increasingly used in biology, considered essential for morphological and phylogenetic studies. They are a quantitative way of studying form based on anatomical landmarks. With this, one can assess morphological variation and explore the usefulness of this method in identifying fossils. Thus, it was possible to refine the taxonomic attributions further. Fossils of Crotalus durissus, Epicrates, an embryo of Boidae, indetermined Viperidae, Tropidurus, and Teiidae were identified. The fossil diversity in the collection area would be expected to be similar to the current local fauna since these are relatively recent materials. However, although most of the identified fossils are consistent with species currently present at the site, the Teiidae vertebra indicates the past occurrence of a species that is no longer present in Rio Grande do Norte. Geometric morphometric analyses corroborate the taxonomic attributions of fossils and are proven a powerful tool in fossil identification. The results of this dissertation are essential for a better understanding of the past faunal composition of Squamata, which had not yet been described for the locality, and to have more information about the paleoenvironment during the Quaternary of Rio Grande do Norte.